Symbolic meanings of totemic images in modern mystical artistic works (Eurasian Journal of Philology Science and Education, 2021)
The authors of the article considered the artistic activity and the specifics of the use of folklore motifs and totemic images in modern mystical artistic works. To determine the symbolic meanings of totem concepts in the stories, the main sources are taken as a basis, demonstrating the relationship and features of literature, myths and folklore. The literary-aesthetic, philosophical, religious aspects and meanings of mysticism are explained. The scientific paradigm presents individual reasoning and concepts regarding artistic mysticism. The authors, along with identifying social problems in mystical micro-plot artistic works published during the period of independence, tried to find out the artistic, poetic activity of folklore genres (legends, myths, magic, fantasy, baksy) used by writers in the process of transmitting thoughts in an allegorical form. For the interpretation of folklore motifs in mystical prose, the artistic works of Tursynzhan Shapai «Sacred tree», Nurgali Oraz «Misplaced tree», Maksat Malikov «Headless wolf», Kanat Abilkair «Zhylan kegi (Revenge of the Snake)» and Lira Konys «Beloved of the Devil» are taken as the object of research, the literary and aesthetic subtext of snake, tree and wolf symbols is analyzed. Along with the activity of folklore totemic concepts as an artistic act in these stories, the role of the utilitarian and educational functions is differentiated from a scientific point of view. The aesthetic activity of legends, mythical totems as an intertextual text in today's Kazakh stories is comprehensively studied and demonstrated in a comparative form. For the first time, the elements that appear under the cross-influence of mystical and folklore motifs in stories are considered. Priority is given to the ways of reviving totemic concepts based on a literary text in the worldview and belief system of the people.Keywords: mysticism, motif, totem, symbol, myth.